Konstitusionalitas Pembatasan Hak Asasi Manusia dalam Putusan Mahkamah Konstitusi - Idul Rishan (The Constitutional Court of the Republic of Indonesia, 2021)
This research try to disscus the Constitutional Court’s interpretation of Article 28J paragraph (2) of the constitution 1945; and the reasons used by constitutional court in declaring an human right limitation unconstitutional. This research is a normative legal research conducted on 19 decisions of constitutional court which contain unconstitutional human right limitation. This research conclude 4 reasons that cause unconstitutional human right limitation, there are; a) To violate the principle of human rights respectation; b) To contain element of discrimination; c) To violate the principle of legal certain; d) Not based on the strong, valid, rational, and proportional reason, and being exessif. Those reasons are alternative, which means that constitutional court can declare an human rights limitation on legislation as the unconstitutional norm only by one from that reasons.